Giant neglected squamous cell carcinoma of the skin. Issue 4 (5th March 2015) - Ricci, Francesco; Paradisi, Andrea; Fossati, Barbara; Mancini, Monica; Curatolo, Pietro; Guerriero, Cristina; Capizzi, Rodolfo
Abstract Nonmelanoma skin cancers (NMSCs) are the most common type of skin tumor, representing about one‐third of all malignancies diagnosed worldwide each year. Cutaneous squamous cell carcinoma (cSCC) is the second most common form of NMSCs and the risk of cSCC invasiveness should be assessed on the basis of tumor size, anatomical location, and histological subtype. Although most cSCCs are early diagnosed and successfully treated, in a small percentage of patients with giant cSCC (maximum diameter >5 cm), metastases may occur; treatment options are limited and not really effective. We report the case of a giant metastatic cSCC that had been neglected for more than 20 years. Radiotherapy or surgery were not feasible and polichemotherapy (cisplatin, 5‐fluorouracil and paclitaxel) was not effective. Therefore, the patient was treated with palliative electrochemotherapy (ECT) achieving a partial reduction of cutaneous metastasis and pain relief but unfortunately the patient died 3 months after the second ECT treatment.